Detoksifikasi hidup anda Josephine Collins ; penerjemah, Ariavita Purnamasari ; editor, Donny Indra R, Theresia Vini S - COLLINS, Josephine; Purnamasari, Ariavita Indra R Donny Vini S, Theresia (2006)
128 hlm ilus 28 cm